Fitting in, standing out navigating the social challenges of high school to get an education - Crosnoe, Robert (Cambridge University Press, 2011)
"In American high schools, teenagers must navigate complex youth cultures that often prize being "real" while punishing difference. Adults may view such social turbulence as a timeless, ultimately harmless rite of passage, but changes in American society are intensifying this rite and allowing its effects to cascade into adulthood. Integrating national statistics with interviews and observations from a single school, this book explores this phenomenon. It makes the case that recent macro-level trends, such as economic restructuring and technological change, mean that the social dynamics of high school can disrupt educational trajectories after high school; it looks at teenagers who do not fit in socially at school, including many who are obese or gay, to illustrate this phenomenon; and it crafts recommendations for parents, teachers, and policymakers about how to protect teenagers in trouble. The end result is a story of adolescence that hits home with anyone who remembers high school"--